Ownership in international vocational education and training transfer: The example of quality development in India - Julia Regel; Muthuveeran Ramasamy; Matthias Pilz (International Journal of Training and Development, 2022)
This article addresses policy transfer in international development activities in vocational education and training. Ownership has been identified and established as a key factor for sustainability of transfer activities in different fields of development cooperation. While the concept has been targeted from a macro-level perspective of government-to-government transfer for a long time, meso- and micro-level perspectives of multi-stakeholder involvement are increasingly emerging. Thus, the focus is on the function of ownership in terms of the role of local stakeholder commitment for sustainable transfer at the level of vocational training institutions in India. Using the example of the transfer of an approach for quality measurement, factors, potentials and challenges for ownership development are explored. Findings are based on the first evaluation cycle of a quality measurement framework developed with specific regard to Polytechnic Colleges and Industrial Training Institutes. Results of the evaluation were analysed considering the model intentions and theoretically based assumptions taken in the research process. Ownership at the meso-level can be established by high degrees of acceptability of measures, participation of stakeholders at the institutional level and internal and external moderation processes in implementation. This paper argues that increased participation and decision-making authority will contribute to measures in line with stakeholders' needs and enable Polytechnic Colleges and ITIs to engage in institutional development more effectively when considering stakeholders' views. This is the case, particularly when focusing on quality assurance and development at the organisational level.
Keywords: 650